Bank Lending to Small and Medium Enterprises : The Republic of Serbia - World Bank (Washington, DC, 2013)
This report presents findings of a study of Bank lending to small and medium enterprises (SME) in Serbia. The study uses methodology developed by the Bank and already used in a number of studies in South America. The study is based on answers to standard questionnaires and detailed on-site interviews with eight banks. The interviewed banks are the most active in SME lending in Serbia and account for about 70 percent of the total market. Banks are currently offering a fairly broad range of both tailored and standardized products and are increasingly flexible with product pricing. This includes checking, savings and time deposit accounts; export and import loans; overdrafts for working capital and investment loans; business credit cards; various types of payment services; Internet and phone banking. The report is organized as follows: section two describes the banking sector and markets in Serbia, reviews definition of SMEs and provides key characteristics of the SME finance market in Serbia. Section three discusses details of SME access to finance. It describes the drivers and obstacles, government programs, and characteristics of the market environment. Section four focuses on how banks engage in lending to SMEs, describing their business models and their risk management. Section five provides a number of conclusions on the conditions of access and future trends.